Alexa, Reshape My Supply Chain: How Voice Commerce Alters Demand Forecasting, Fulfillment Speed, and Marketing Messaging: JEL Classification: D91; L81; M15; M31; O33 - Simon Dzreke; Semefa Elikplim Dzreke (Generasi Sains Indonesia, 2026)
The simple utterance